2021
DOI: 10.31603/ce.4925
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the application of therapeutic group therapy (TKT) for school-age children in Delima, Pekanbaru

Abstract: Children are highly prone to certain psychological challenges, particularly at elementary level. These problems are predominantly influenced by environmental and academic conditions. Therefore, this research aims to stimulate the growth and development of school-age children from various perspectives. This activity was conducted at Al-Qur'an Education Park, Baitul Arsy Mosque, Hamlet 008, Delima village, Tampan sub-district, Pekanbaru, between September-December 2020. Additionally, the class II-VI students wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This is consistent with the application of research in community service by Widyaningrum et al (2020) showing that the Therapeutic Group Therapy of school-age children affected on the knowledge skills and industrial development of school-age children. Intervention done by Usraleli et al (2021) also demonstrated that after receiving TGT, school children comprehended and were able to carry out their developmental tasks in the areas of motor, cognitive, language, emotion, personality, moral, spiritual, and psychosocial development, as well as increase self-confidence in making friends with peers and improve the ability to accept lessons at school. Yektiningsih et al (2021) proved that TGT for schoolchildren benefited motor, cognitive, and linguistic development, as well as emotional and personality development and psychosocial development.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is consistent with the application of research in community service by Widyaningrum et al (2020) showing that the Therapeutic Group Therapy of school-age children affected on the knowledge skills and industrial development of school-age children. Intervention done by Usraleli et al (2021) also demonstrated that after receiving TGT, school children comprehended and were able to carry out their developmental tasks in the areas of motor, cognitive, language, emotion, personality, moral, spiritual, and psychosocial development, as well as increase self-confidence in making friends with peers and improve the ability to accept lessons at school. Yektiningsih et al (2021) proved that TGT for schoolchildren benefited motor, cognitive, and linguistic development, as well as emotional and personality development and psychosocial development.…”
Section: Discussionmentioning
confidence: 97%
“…Therapeutic Group Therapy conducted by Usraleli et al (2021) revealed that children understand more and are better equipped to carry out their developmental responsibilities in the areas of motor, cognitive, linguistic, emotion, personality, moral, spiritual, and psychosocial development, as well as boost their self-confidence. School-age children get therapeutic group treatment that stimulates their motor, cognitive, verbal, emotional, personality, moral, spiritual, and psychosocial development.…”
Section: Discussionmentioning
confidence: 99%